International academic representation of traditional Chinese medicine in the post-COVID-19 era: a corpus-based exploration - Pan, Jiejing (Frontiers in Communication, 2025)
IntroductionTCM has long been subject to international debates regarding its scientific validity, highlighted by studies of its portrayal in particularly media discourse revealing Western perceptions of TCM as “lacking evidence.” The COVID-19 pandemic, however, has markedly increased global attention towards TCM, prompting a re-evaluation of its role.MethodsCorpus-assisted discourse analysis was employed, with WordSmith 8.0 utilized, to examine perceptions of TCM within international English academic literature from 2020 to 2022 across diverse regions and disciplines.ResultsThis study identified three major findings: (1) In the specific context of COVID-19, representations of TCM are consistently positive across all regions, emphasizing its historical credibility, theoretical depth, and perceived efficacy in pandemic response. (2) TCM is represented differently across geographical regions—Asian scholars frequently characterize it as “versatile, reliable, and influential,” while European scholars label it a “non-scientific marginal therapy.” North American and Australian perspectives portray TCM as a dual-sided coin which potentially serves as an “adjuvant alternative,” whereas African scholars seem skeptical, perceiving it as a “low-end therapy.” (3) Disciplinary variation is also observed, with medicine, science, engineering, agronomy and humanities displaying distinct research foci and thus representational tendencies.DiscussionThese findings underscore the complex interplay between medical systems, cultural and geographic proximity, institutional factors, status quos of TCM research and practice as well as disciplinary conventions in the international academic representation of TCM, which contribute valuable insights into its evolving global scientific status and integration into modern healthcare.